Four Facts Concerning Competition in US Generic Prescription Drug Markets. Issue 1 (2nd January 2020) - Conti, Rena M.; Berndt, Ernst R.
Abstract: We establish four facts concerning competition among US generic drug suppliers, using IQVIA's National Sales Perspective™ 2004 Q4–2016 Q3 data. We define a unique product market ("molform"), consisting of the combination of a molecule active ingredient and a route of administration formulation, aggregated over different doses and strengths. We find: (1) supply exhibits substantial churning in entrants and exits; (2) volume-weighted use concentrates in older generic molform cohorts; (3) the extent of competition is greatest for the oldest molform cohorts and is smallest for the youngest molform cohorts. With a median of one competitor, the extent of competition in the youngest molform cohort is very limited; and (4) supplier-molform annual revenues are typically small, are largest for relatively young drugs, but are heavily right skewed. These four facts provide an empirical platform on which to construct and empirically evaluate hypotheses regarding generic drug market structure, performance, and possible policy reforms.